B33– and B34–: Aromatic Planar Boron Clusters with a Hexagonal Vacancy - Chen, Qiang; Li, Wei‐Li; Zhao, Xiao‐Yun; Li, Hai‐Ru; Feng, Lin‐Yan; Zhai, Hua‐Jin; Li, Si‐Dian; Wang, Lai‐Sheng (European journal of inorganic chemistry, 2017)
Systematic experimental and theoretical studies have shown that anionic boron clusters (Bn–) possess planar or quasi‐planar (2D) structures in a wide range of cluster size. The 2D structures consist of B3 triangles often decorated with tetragonal and pentagonal defects. As n increases, hexagonal vacancies appear to be a key structural feature, which underlies the stability of borophenes. The correlation of the defects with cluster size is important to understand the stability and structural evolution of boron clusters. Here we report an investigation of the structures and chemical bonding of B33– and B34– using photoelectron spectroscopy (PES) and density functional theory (DFT) calculations. Global minimum searches reveal that the potential landscapes of B33– and B34– are dominated by 2D isomers. Comparisons between experiment and theory confirm that their global‐minimum structures are both 2D with a hexagonal vacancy (Cs B33–) and (C1 B34–), the latter being a chiral cluster. Bonding analyses indicate that the Cs B33– cluster possesses ten delocalized π bonds, analogous to those in the polycyclic aromatic hydrocarbon C19H11–. Bonding analyses on the equivalent closed‐shell B342– species show that its 12 delocalized π bonds consist of two separate aromatic systems: nine exterior and three interior π bonds. A joint photoelectron spectroscopy and theoretical study is used to probe the structures and chemical bonding of the B33– and B34– clusters. Both clusters are found to be planar with a hexagonal vacancy, providing key links in understanding the structural evolution of boron clusters. Chemical bonding analyses show that both clusters are aromatic with π bonding similar to polyaromatic hydrocarbons.